1998
DOI: 10.1177/0263211x98262003
|View full text |Cite
|
Sign up to set email alerts
|

The Role Perceptions of Government and Non-Government Headteachers in Pakistan

Abstract: Relatively little systematic research has been undertaken on the role of the principal/headteacher in developing countries. In this study six headteachers of government and non-government secondary schools in Karachi were interviewed in depth and five completed diaries of their activities for one week. The study drew upon Rosemary Stewart's analysis of management roles in terms of the demands and constraints which are placed upon managers and the ways in which available choices are exercised by them. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 9 publications
2
28
0
Order By: Relevance
“…The Ministry of Education (MOE) in many countries (e.g. China, Thailand, Singapore, Malta, Nigeria, Pakistan) designs a unified national curriculum, syllabus, materials and exams and guides funding and staffing of schools, including teacher selection, recruitment and staff development (Uwazurike, 1991;Fenech, 1994;Hallinger et al, 1994;Ligget et al, 1997;Simkins et al, 1998;Morriss et al, 1999). Fenech (1994) illustrated this feature by the Maltese example: 'The allocation of teachers to the various classes in the school is perhaps the only organizational decision which is left in the hands of the principals' (p. 131).…”
Section: The Portrait Of Principalship In Developing Countriesmentioning
confidence: 99%
See 3 more Smart Citations
“…The Ministry of Education (MOE) in many countries (e.g. China, Thailand, Singapore, Malta, Nigeria, Pakistan) designs a unified national curriculum, syllabus, materials and exams and guides funding and staffing of schools, including teacher selection, recruitment and staff development (Uwazurike, 1991;Fenech, 1994;Hallinger et al, 1994;Ligget et al, 1997;Simkins et al, 1998;Morriss et al, 1999). Fenech (1994) illustrated this feature by the Maltese example: 'The allocation of teachers to the various classes in the school is perhaps the only organizational decision which is left in the hands of the principals' (p. 131).…”
Section: The Portrait Of Principalship In Developing Countriesmentioning
confidence: 99%
“…It is hardly surprising, then, that a Pakistani principal considered himself to be a doorman only (Simkins et al, 1998), and Hokal and Shaw (1999) concluded that the role of principals in the United Arab Emirates is thus made insignificant and ritualized, at any rate by 'western standards' (p. 177).…”
Section: Downloaded By [Florida Atlantic University] At 08:30 21 Novementioning
confidence: 99%
See 2 more Smart Citations
“…Quality teachers need quality educational leaders who are well equipped to bring positive change within the school system [2]. Therefore, this study is significant as its findings may provide alternative structures and strategies towards improving the quality of professional development programmes within the Pakistani context.…”
Section: Research Rationalmentioning
confidence: 96%